Social disorganization and gender equality as correlates of family violence and rape - Goodson, Amanda (Journal of crime and justice, 2019)
Social disorganization theory suggests residential instability, ethnic heterogeneity, family disruption, and low socioeconomic status will positively predict crime in a community. Much of the earlier work on social disorganization has focused on crimes committed outside of the home. More recently, studies have used the social disorganization theoretical framework to explain rates of more intimate crimes, such as domestic violence, rape, and family violence. However, the majority of this research has failed to account for other community correlates of crime, such as women’s absolute status and gender inequality, which have been shown to affect rates of interpersonal violence, particularly violence against women. The purpose of the current study is to extend the literature by examining the associations between social disorganization, women’s absolute status, gender inequality, family violence, and forcible rape. The sample consisted of 254 counties in Texas, and analyses examined the associations between social disorganization measures, women’s absolute and relative status, and counts of family violence and rape. Using a series of negative binomial regression models, results for family violence and forcible rape provide only partial support for social disorganization after controlling for women’s absolute status and gender equality.